Patient satisfaction and outcomes of crisis resolution home treatment for the management of acute psychiatric crises: a study during the COVID-19 pandemic in Madrid - Moreno-Alonso, Irene; Nieves-Carnicer, Manuel; Noguero-Alegre, Alexandra; Alvarez-Mon, Miguel Angel; Rodriguez-Quiroga, Alberto; Dorado, Juan F.; Mora, Fernando; Quintero, Javier (Frontiers in Psychiatry, 2023)
Background: Crisis Resolution Home Treatment (CRHT) seem to offer comparable results to the traditional hospitalization model, at a lower cost and offering greater flexibility and scope. However, in Madrid, its implementation in Mental Health did not occur until the midst of the COVID-19 pandemic. In this work we analysed the effectiveness of a mental health CRHT unit promoted during the COVID-19 pandemic, as well as the degree of satisfaction of patients and their families. Methods: 90 patients were treated by the CRHT unit in the period between October 2020 and June 2022. All patients met the inclusion criteria: 1) Acute psychopathological decompensation in patients suffering from psychotic disorders, major affective disorder, obsessive compulsive disorder, personality disorder and other severe mental disorders causing functional disability, according to ICD-10 diagnostic criteria; 2) Ages between 18-90 years old; 3) Living in the urban area of Vallecas, Madrid; and 4) Counting with sufficient social and family support. The effectiveness of the intervention was evaluated with the SF-36 health questionnaire, the caregiver burden with the Zarit questionnaire, and patient satisfaction with a survey specifically designed for this work. Results: 55 (61.1%) patients completed the SF-36 at baseline and at the end of hospitalization. Statistically significant improvements were observed in the 8 dimensions of the SF-36 (P<0.05). However, CRHT did not achieve a statistically significant decrease in caregiver burden. Regarding the satisfaction of the patients with the attention and care received, an average score of 47.72/50 was obtained. Conclusions: The Crisis Resolution Home Treatment intervention resulted in significant improvement in patients' quality of life with high satisfaction scores. However, it did not effectively reduce caregiver burden. Future research should focus on randomized controlled trials with long-term follow-up to assess the effectiveness of CRHT compared to traditional hospitalization and utilize specific assessment scales for different mental disorders.